The rise of lobbying and interest groups in the states during the Progressive Era - Chamberlain, Adam; Strickland, James; Yanus, Alixandra B. (Frontiers in Political Science, 2023)
The postbellum rise of voluntary, federated associations set the stage for modern pressure politics in the American states, yet the connection between associations and lobbying in this era is grossly understudied. Relying on associations' own records and a new dataset of state lobbyists, we explore this relationship more deeply, documenting how federated associations gained membership, created political agendas, and lobbied state legislators for reform. To understand better the processes linking group strength with direct lobbying, we present descriptive case studies of the Grange (agriculture), the “Big Four” railroad brotherhoods (skilled labor), and the American Bankers' Association (finance). Our findings reveal how group strength, measured by association membership or local organizing, was not always related to the choice to lobby legislatures directly. These findings suggest pathways for future research comparing Progressive Era associations to one another, as well as showing how their actions parallel those of modern pressure groups. This analysis also paves the way for a more robust temporal understanding of lobbying in the American states.